Veja, Istoé e Época: recontando a história no universo midiático. - Assis, Edjane Gomes de (2010)
The history rewritten by the historians of the moment Veja, Istoé and Época reappears through strategies that mean the discursive happening. This research could conduce us to see that the form how the media discourses rewrite a history is submitted to representation games, and to all the technical set, graphic apparatus, images, an intericonicity/interdiscursivity that delineates the sayings. Such vehicles from where history is retold, speak from places, spaces determinated in the social environment. They retake, through register, tracks from other discourses, knowledges form other times to construct meanings. Although they make use of an ideology towards to the new in the immediate moment, we observe in the magazines discourses, a reproduction of old discourses immortalized in the traditional history. The sayings produced by the media establish meanings in the imaginary of the subjects and the narrated histories reproduce the ideology of the winner. The discourses reappear full of values that distinguish the sovereignty discourse, the progress, the modernity and, at the same time, reproduce values stigmatized in the social instances. The journalists on this way, tell the facts from a place and determinated position. We could verify, with the theoretical support of Discourse Analysis from the French line and, above all, how the foucaultian look under the discourses and the registers, a history that comes through movements of other discourses that constitute meanings in the social setting. And, so, we can reflect about the effects that are established in the opacity of the tests from the three magazines identifying the social, historical and ideological aspects that constitute such issues, analyzing the truths and the truth games that sustain the sayings.